THE EFFECT OF GAMIFICATION IN LEARNING ON STUDENTS’ READING COMPREHENSION - Sari, Novita; AkbarJono, Ali; Martina, Feny (JPT : Jurnal Pendidikan Tematik, 2022)
This research aims to determine whether there is an effect of gamification in learning on students reading comprehension on eighth grade students at SMP PANCASILA Bengkulu. This research uses a Quasi-Experimental method with the type of research being quantitative. The researcher decided to do an experiment in grade 8 with a total of 32 students. In the process of collecting data, researchers conducted a pre-test and post-test for 4 meetings. From the results of this study, the students' average pre-test score was 7.55 and the post-test average was 8.96, which means that the post-test score was higher than the pre-test score. With a standard deviation of 0.336 pre-test and 0.40 pos- test. So, it can be concluded that the application of the gamification in learning method has a significant influence on the eighth-grade students of SMP PANCASILA Bengkulu.